Utilização do rejeito de sinter feed como agregado na produção de peças de concreto para pavimentação - Ayrton Vianna Costa (2009)
This work deals with sinter feed tailing studies and technical and ecological convenience employment and exploitation feasibility proceeding of iron ore activities, as an aggregate in the concrete production to the pavement precast elements manufacture. As a result of the themes restricted bibliography, the search was developed based on the traditional aggregates knowledge and in a few tailing usage practical experiences known in this area and, mainly, based on the referred tailingchemical analyses and physical tests in the specific parts produced performance. Due to this boarding, the theme is unprecedented. Initially, it was performed tailing physical and chemical wide range tests, constituting the tailing characterization research step, which has been completed with the mortar simple compressive strength test. Later, in the small concrete block production step, parts were made at an industry process line and subjected to Brazilian standardized precast tests. In both steps, results were quite satisfactory, proving the research objectives. The best relevance of using the sinter feed tailing as an aggregate in producing concrete pavement parts is related to the construction industry sustainable development. By the side of mining industries, the productively way of that tailing disposition means large cost-benefit relationship characterized as the absence of piles in their areas as their operational cost absence